POLICY IMPLEMENTATION OF EDUCATIONAL ACCELERATION PROGRAM IN SENIOR SECONDARY SCHOOL (The Study at SMA Negeri 1 Lamongan) - Mifakhul Af’ida, Fitri (FIA UB, 2015)
Policy Implementation Of Educational Acceleration Program In Senior Secondary School (The Study at SMA Negeri 1 Lamongan). In this era of globalization of education sounds very important, because education is a vehicle or instrument if used not only to liberate mankind from backwardness, but also from ignorance and poverty. Whereas each student have different need, intelligence, skills, interests, and talent. To do it so Indonesian government implement of Education Service through Acceleration Program. In connection with that, researcher want to know more about policy implementation of education service Â with by studying the implementation of acceleration program especially in SMA Negeri 1 Lamongan. The objective of this study is to describe, interpretate, and analyze how the policy implementation of educational acceleration program in senior secondary school. This research uses qualitative approach using descriptive method. The Result of this study show that Policy Implementation of Educational Acceleration Program at SMA Negeri 1 Lamongan has been going well according to the Guidlines and regulations, this is proven with the procedures acceleration program consist of identification of student, curriculum, quality of teacher, facilities and infrastructure, evaluation system, supervisors and coenceling, expense, school comitte and education council. All those procedures had suitable with strategy of implementation of acceleration program that Â implemented at SMA Negeri 1 Lamongan.